STUDYING THE VARIATION BETWEEN WOOD TENSION AND COMPRESSION AT DIFFERENT STEM LENGTHS AND DIAMETER LEVELS IN PHYSICAL PROPERTIES OF MELIA AZEDARACH L. AND PINUS BRUTIA TEN. LEANING STEMS - Almalah, A. R. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to find the main differences in physical properties between tension wood of Melia azedarach L. and compression wood of Pinus brutia Ten. and comparing them to the normal wood of the standing trees. Results indicate that tension and compression wood increased swelling (length, volume and thickness) after immersion of samples in water for 2, 6 and 24 hours and volumetric shrinking percentage greater than normal wood. Also, tension wood of Melia azedarach L. gave greater volumetric and thickness swelling percentage than compression wood of Pinus brutia Ten. Results did not show clear differences between tension and compression wood in longitudinal swelling percentage. Also, results showed that the eccentric of the stem pith of both tension and compression wood of the leaning trees was the highest at the stem base, then the eccentric of the pith will decrease gradually from base to the stem top. The main average of volumetric and thickness swelling after immersion in water for 2, 6 and 24 hours of heartwood for both Melia azedarach L. and Pinus brutia Ten. was lower and insignificant compared to sapwood.